MANAGEMENT OF MULTIPLE FRACTURES IN OSTEOGENESIS IMPERFECTA PATIENTS IN REGIONAL HOSPITAL OF RURAL AREAS: WHAT AN ORTHOPEDIC SURGEON CAN DO? - zukhruful muzakkie; Doli Mauliate Sitompul (Jurnal Medika Hutama, 2026)
ABSTRACT Background: Osteogenesis Imperfecta (OI) is a connective tissue disorder characterized by bone fragility and recurrent fractures. Managing fractures in OI patients in rural regions poses challenges due to limited resources and high treatment costs. Objective: To describe the management of pathologic fractures in a pediatric patient with OI who resides in a remote area. Case Summary: An 8-year-old girl with known OI presented with pain and deformity of the right lower leg after falling from a stroller. Radiographs confirmed closed fractures of the tibia and fibula. The ideal management is Fassier-Duval intramedullary rodding; however, due to socioeconomic limitations and lack of facility availability, closed reduction and immobilization were performed. Conclusion: Management of fractures in OI should be individualized. In resource-limited settings, closed reduction and immobilization may be an acceptable alternative. Keywords: Osteogenesis imperfecta, pediatric fracture, rural hospital, closed reduction, pathologic fracture.